2009
DOI: 10.1093/schbul/sbp083
|View full text |Cite
|
Sign up to set email alerts
|

Psychotic-Like Experiences in Major Depression and Anxiety Disorders: A Population-Based Survey in Young Adults

Abstract: While psychotic-like experiences are usually associated with psychotic disorders, individuals with depression and anxiety are also more likely to report these symptoms compared with well individuals. Psychotic-like experiences are associated with a range of common mental disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

16
204
2
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 242 publications
(223 citation statements)
references
References 40 publications
16
204
2
1
Order By: Relevance
“…This is, in fact, in line with recent research, which suggests that psychotic symptoms reported both in the clinic and in the community index risk for a much wider range of psychopathology than psychotic disorders (Addington et al, 2011, Kelleher et al, 2011b, Lencz et al, 2004. Varghese et al, (2011 Two recent studies suggest that age is an important factor in the relationship between psychotic symptoms and psychopathology. Bartels-Velthuis et al, (2010) found that auditory hallucinations in children aged 7 to 8 years demonstrated only a minor association with psychopathology as measured by the Child Behavior Checklist (CBCL).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…This is, in fact, in line with recent research, which suggests that psychotic symptoms reported both in the clinic and in the community index risk for a much wider range of psychopathology than psychotic disorders (Addington et al, 2011, Kelleher et al, 2011b, Lencz et al, 2004. Varghese et al, (2011 Two recent studies suggest that age is an important factor in the relationship between psychotic symptoms and psychopathology. Bartels-Velthuis et al, (2010) found that auditory hallucinations in children aged 7 to 8 years demonstrated only a minor association with psychopathology as measured by the Child Behavior Checklist (CBCL).…”
Section: Discussionsupporting
confidence: 87%
“…More recently, evidence has been emerging that the clinical significance of psychotic symptoms extends beyond psychosis, with a number of research groups finding that young people who endorse questionnaire items on psychotic symptoms are also more likely to endorse symptoms of non-psychotic psychopathology, especially symptoms of depression (Hanssen et al, 2003, Johns et al, 2004, Kelleher et al, In Press, Nishida et al, 2008, Polanczyk et al, 2010, Scott et al, 2009b, Varghese et al, 2011, Wigman et al, 2011, Yung et al, 2009.…”
Section: Introductionmentioning
confidence: 99%
“…18 Affective disturbances, more generally, have been shown to be linked to PE across different stages along the psychosis continuum. [19][20][21][22][23][24][25] Cognitive models of psychosis provide a detailed specification of the cognitive processes associated with emotional responses to stress and consider cognitive biases, such as a hypervigilance for threat, to be involved in stress reactivity. 4, 26 First, stressful experiences per se may alter cognitive interpretation and bias individuals toward hypervigilance for threat.…”
Section: Introductionmentioning
confidence: 99%
“…This is supported by high levels of affective dysregulation in clinical psychosis (e.g. Buckley et al 2009) and, vice versa, frequent reports of psychotic symptoms in affective disorders (Hanssen, et al 2003;Varghese et al 2011;Wigman et al 2012). Considerable overlap in symptom expression is one of the most important arguments that categorical models may not adequately describe psychopathology as it exists in nature (Kendell & Jablensky, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Symptoms of psychosis (Hanssen et al 2003;Varghese et al 2011;Kelleher et al 2012b;Wigman et al 2012) and bipolar disorder (Angst et al 2010;Nusslock & Frank, 2011), at clinical and subclincal levels of expression, commonly occur in the context of major depressive disorder (MDD). This reflects overlap between affective and psychotic disorders in genetic ) and environmental risk factors (Weiser et al 2005), as well as in underlying endophenotypes, for example (neuro)cognitive, social and emotional dysfunctions (Weiser et al 2005;Hill et al 2009;Simonsen et al 2011).…”
Section: Introductionmentioning
confidence: 99%